(untitled) (Marketing Journal, 2026)
Abstract The study examined customer-oriented marketing strategies aimed at expanding the deposit portfolio of commercial banks from both theoretical and practical perspectives. The impact of customer segmentation, personalized service delivery, and digital marketing tools on deposit volumes in the banking sector was analyzed. The deposit dynamics of Uzbekistanʼs commercial banks during 2019-2024 were assessed based on quantitative indicators. The research findings demonstrated that a differentiated marketing approach grounded in thorough analysis of customer needs significantly enhanced deposit mobilization efficiency. Practical recommendations were developed for implementing CRM systems, expanding financial literacy programs, and diversifying digital channels. Keywords: deposits, commercial banks, marketing strategy, customer orientation, CRM, digital marketing, banking services, financial literacy